2005
DOI: 10.1021/ie050149p
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Deposit Formation from “Waxy” Mixtures via Moving Boundary Formulation:  Radial Heat Transfer under Static and Laminar Flow Conditions

Abstract: A mathematical formulation, based on heat transfer considerations, is presented for solids deposition from “waxy” or paraffinic mixtures. The proposed unsteady-state model uses the moving boundary problem approach for investigating the deposit-layer growth in a circular pipe from binary eutectic mixtures of n-C16H34 and n-C28H58. The model equations were solved numerically to explore the deposition behavior and the growth of deposit layer with time in the radial direction under both static and laminar flow con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(147 citation statements)
references
References 32 publications
10
135
0
2
Order By: Relevance
“…Without such assumptions, the numerical solution methodology can become complex and time-consuming. 17 Model Description. When a cold finger assembly is inserted into a waxy mixture or crude oil (with the inside of the cold finger exposed to a cooler temperature lower than the WAT of the waxy mixture), a deposit layer would start to form on the outer cold finger surface due to a partial freezing process.…”
Section: ■ Unsteady-state Heat-transfer Modelmentioning
confidence: 99%
“…Without such assumptions, the numerical solution methodology can become complex and time-consuming. 17 Model Description. When a cold finger assembly is inserted into a waxy mixture or crude oil (with the inside of the cold finger exposed to a cooler temperature lower than the WAT of the waxy mixture), a deposit layer would start to form on the outer cold finger surface due to a partial freezing process.…”
Section: ■ Unsteady-state Heat-transfer Modelmentioning
confidence: 99%
“…The growth of a wax deposit layer is accompanied by the release of the latent heat of phase change. The moving boundary problem formulation has been used for developing mathematical models based on the heat‐transfer approach . In the heat‐transfer approach, the liquid‐deposit interface temperature is taken to be equal to the WAT of the wax solution throughout the deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…The moving boundary problem formulation has been used for developing mathematical models based on the heat-transfer approach. [18,[26][27][28][29] In the heat-transfer approach, the liquid-deposit interface temperature is taken to be equal to the WAT of the wax solution throughout the deposition process. Batch cooling studies under static and sheared conditions [30,31] and bench-scale flow-loop studies [15][16][17][19][20][21][22] have confirmed the interface temperature (T d ) to remain constant, and close to the WAT, during the gelling and deposit-growth periods.…”
Section: Introductionmentioning
confidence: 99%
“…In the actual wax deposition loop, the temperature distribution will appear not fully development, so it is necessary to solve the problem of hot inlet. In order to obtain the temperature distribution of the loop test section, the usual method is dimensionless energy balance equation and boundary condition by introducing dimensionless parameters, then the temperature field distribution of the analytical solution can be obtained after proper simplification (The form of Bessel function), the solution process is more complex (Zhu G J., 1989;Li et al, 2014;Saracoglu et al, 2000;Bhat et al, 2005). In addition to this Bessel function method, the temperature distribution of the test segment can be obtained by using Handal method for the heat transfer characteristics of the tested tube of wax deposition loop (Handal A D., 2008).…”
Section: Introductionmentioning
confidence: 99%